2011
DOI: 10.1111/j.1745-4565.2011.00340.x
|View full text |Cite
|
Sign up to set email alerts
|

ENTEROTOXIN GENE PROFILE AND ANTIBIOGRAM OF BACILLUS CEREUS STRAINS ISOLATED FROM RAW MEATS AND MEAT PRODUCTS

Abstract: The present investigation was undertaken to study the incidence and antibiogram of enterotoxigenic Bacillus cereus in raw meats and meat products. B. cereus was isolated from 97 (37.45%) of the 259 samples analyzed. Recorded incidences of B. cereus from chicken, chevon, mutton, meat products and swab samples were 33.33, 37.20, 39.47, 51.85 and 26.08%, respectively. Screening of isolates by multiplex polymerase chain reaction revealed the overall distribution of various enterotoxin genes hblD, hblA, hblC, nheA,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
2
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 28 publications
1
11
2
2
Order By: Relevance
“…1, 018,935,884,759,695,618,565,486 indicates hblD, nheB, hblA, nheA, hblC, nheC, cytK and entFM, respectively 10 2 cfu/g to 3.90×10 4 cfu/g in meat products. In support of this, Rather et al (2012) reported similar level of contamination in raw meat but found higher in meat products. Thus, if carcasses are not stored properly, the population of B. cereus may multiply to dangerous levels exceeding 1×10 6 cfu/g within the short span of time.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…1, 018,935,884,759,695,618,565,486 indicates hblD, nheB, hblA, nheA, hblC, nheC, cytK and entFM, respectively 10 2 cfu/g to 3.90×10 4 cfu/g in meat products. In support of this, Rather et al (2012) reported similar level of contamination in raw meat but found higher in meat products. Thus, if carcasses are not stored properly, the population of B. cereus may multiply to dangerous levels exceeding 1×10 6 cfu/g within the short span of time.…”
Section: Discussionsupporting
confidence: 56%
“…The entFM gene was the common enterotoxin gene found in 27 (93 %) B. cereus isolates in this study, Ngamwongsatit et al (2008) also found this gene in all tested isolates of B. cereus. The gene for cytK was found in 12 (41.4 %) of the isolates whereas Wijnands et al (2006), Ngamwongsatit et al (2008, Chitov et al (2008) and Rather et al (2012) detected it in 50, 88, 70.40 and 65.98 % of their isolates, respectively.…”
Section: Discussionmentioning
confidence: 98%
“…One of the most recent ones were developed by Rather et al (2011) in India addressing raw and pasteurized milk and the detection of HBL genes. In that study the percentages of detection for hblA , hblC and hblD were around 70% for the tested samples.…”
Section: Resultsmentioning
confidence: 99%
“…However, it has a short life storage time due to some deterioration during storage especially lipid and protein oxidation and microbial contamination (Yalçın, Alçay, Yüzbaşıoğlu, Çakmak, & Sağlam, ). Previous studies have indicated that it is very vulnerable to numerous foodborne pathogens especially L. monocytogenes , S. aureus , and B. cereus (Rather, Aulakh, Gill, & Ghatak, ; Tewari, Singh, & Singh, ).…”
Section: Introductionmentioning
confidence: 99%
“…pathogens especially L. monocytogenes, S. aureus, and B. cereus (Rather, Aulakh, Gill, & Ghatak, 2012;Tewari, Singh, & Singh, 2015).…”
mentioning
confidence: 99%